Vanadium Transport through Cation and Anion Exchange Membranes. (25th June 2020) - Darling, Robert M.; Saraidaridis, James D; Shovlin, Christopher; Fortin, Michael
Abstract : Transport of vanadium ions (V 2+ plus V 3+ ) and water through Nafion® and the anion exchange membrane Fumasep FAPQ-330 were measured as functions of current density in a triple membrane cell. The amount of vanadium moving through FAPQ was an order of magnitude less than through Nafion® at all current densities. A large amount of water, -1.5 moles per mole of univalent positively charged ions, was transferred through FAPQ in the direction opposite to vanadium and current. Relatively little water moved through Nafion® at the same operating conditions.